An analysis of reference queries and answer-providing sources at the Filipiniana Section of the University of the Philippines Main Library, 1981-1983 - Mallari, Florenda D.; Buenrostro, Juan Jr. C.; Hidalgo, Namnama P. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 1984)
Reference work has been one of the major functions of the senior staff at the Filipiniana Section in the University of the Philippines Main Library. Through the years, this kind of service has been reflected in the annual reports only by the statistics of reference books and pamphlets used and in the number of reference questions handled by the reference staff. For a better understanding of this reference function, an analysis of reference questions was conducted to: 1) find out the types of questions asked by library inquirers at the Filipiniana Section; 2) identify the modes of transaction employed in referring the questions to the reference librarians; 3) determine the types of information or subjects inquirers generally looked for; 4) identify the answer-providing sources consulted by the librarians in answering the queries; 5) determine the cause/s of failure to answer some questions; and 6) identify the weaknesses of the reference service and make recommendations for improvement.
The descriptive method of research was employed. One-thousand four-hundred twenty-two reference questions received during two academic years at the Filipiniana Section in the University of the Philippines were the data used in this study. Tables showing percentages and rankings were used in the analysis and interpretation of data.
The findings revealed that out of the 5,980 questions directed to the reference librarians during the period under study, only 1,422 were ready reference, advisory and research types. The questions were mostly categorized as background, bibliographical, trend, biographical, fact, and exact reproduction types. Questions were heavily concentrated on these subjects: Philippine history, Philippine languages and literatures in the Tagalog language, and in the social sciences, specifically education, economics, population, politics and government, and sociology. Questions pertaining to psychology, military and naval sciences, agriculture and veterinary medicine were very minimal. Most of the answers to the queries were found in periodicals, circulation books and pamphlets, reference books and newspapers. One-hundred sixty-five questions or about 11 percent of the 1,422 were unanswered. Among the reasons for the failure to answer these questions were: 1) the needed information/data could not be found in the existing collection; 2) the requested material has not been acquired by the library; 3) the material desired by the inquirer was too recent or was still for printing; 4) the material that would answer the questions was missing at the time of request; and 5) an index to periodicals for the very recent information needed by the inquirers was not available.
Based on the findings of this study, the following recommendations are made to further improve reference service in the Filipiniana Section: 1) the Guide to the Filipiniana Section, 1980, must be updated to minimize directional questions caused by recent changes in the setup and procedures of the Section; 2) analytics of collective works, anthologies, and papers and proceedings of conferences, workshops, seminars, etc. should be produced to reduce searching time for requests which call for the use of these materials; 3) a collection development staff should be formed to evaluate the present collection and, if possible, staff with subject specialization in various branches of knowledge should be recruited to ensure a balanced acquisition of materials; 4) the indexing of periodicals and printing of the Index to Philippine Periodicals should be up-to-date; and 5) unanswered reference questions should be further studied and analyzed to see if there is a possibility of solving them for the benefit of future inquirers on the same subject or material.
Special Problem (Master of Library Science)--University of the Philippines Diliman
Keywords: University of the Philippines (Diliman) Main Library. Filipiniana Section; Reference service (Libraries).